도재전장주조관에 사용되는 도재의 색안정성에 관한 연구 - 류소영; 임주환; 조인호; Ryu, So-Young; Lim, Ju-Hwan; Cho, In-Ho (Taehan Chikwa Poch'ol Hakhoe chi, 2000)
Dental porcelain should have adequate strength and similar esthetics as natural teeth. Recently esthetics has become a high priority in clinical dentistry. Thus the evaluation of color stability of dental porcelain has become an important part in dental research. The purpose of this study was to evaluate the difference in color stability of 3 types of porcelain(Vintage, VMK 95, CERAMCO II). The porcelain were divided into groups by 2 types of treatment(glazing or non-glazing and thermocycling or non-thermocycling). The porcelain were dyed with methylene blue and distilled water, and then the color stability was evaluated with a spectrophotometer The results were as follows; 1. The color change of porcelain increased in the order of VMK 95, Vintage, CERAMCO II. But there was no significant difference. 2. The color change decreased in the glazing group compared to the non-glazing group(p<0.05). 3. The color change increased after thermocycling But there was no significant difference. 4. The color change according to dye method was significantly larger with methylene blue copared to distilled water(p<0.05).